Online student evaluation improves Course Experience Questinnaire results in a physiotherapy program - Tucker, Beatrice; Jones, Sue; Straker, Leon (Routledge, 2008)
This paper reports the use of an online student evaluation system, Course Experience on the Web (CEW), in a physiotherapy program to improve their Course Experience Questionnaire (CEQ) results. CEW comprises a course survey instrument modeled on the CEQ and a tailored unit survey instrument. Closure of the feedback loop is integral in the CEW system. Analysis of the data shows that the students' evaluation in their final year of the program is closely correlated with their CEQ results. Increases in the CEQ scores from 2001-04 included an increase in the Good Teaching Scale (27.5), Generic Skills Scale (10.3) and Overall Satisfaction Index (29.3). By using CEW, academics at the School of Physiotherapy were able to determine students' perceptions during the course, make changes to teaching and learning, where appropriate, in a timely manner and, as a result, the CEQ scores were improved markedly. (Contains 2 tables and 4 figures.)